Higher serum testosterone levels predict poor prognosis in castration‐resistant prostate cancer patients treated with docetaxel. Issue 3 (9th December 2019) - Ando, Keisuke; Sakamoto, Shinichi; Takeshita, Nobushige; Fujimoto, Ayumi; Maimaiti, Maihulan; Saito, Shinpei; Sanjyon, Pae; Imamura, Yusuke; Sato, Nobuo; Komiya, Akira; Akakura, Koichiro; Ichikawa, Tomohiko
Abstract: Background: The role of testosterone as a prognostic factor for castration‐resistant prostate cancer treated with docetaxel in Japan was investigated. Methods: A total of 164 patients with castration‐resistant prostate cancer who received docetaxel treatment at Chiba University Hospital and an affiliated hospital were retrospectively analyzed. Testosterone and other clinical factors at the start of docetaxel treatment were evaluated with respect to overall survival and progression‐free survival. Results: Of the 164 patients, 69 had high‐volume tumors. The median prostatic‐specific antigen was 27.0 ng/mL. The median testosterone was 13.0 ng/dL. The rates of bone and visceral metastases were 80.1% and 8.8%, respectively. For progression‐free survival, testosterone ≥13 ng/dL was an independent prognostic factor only on univariate analysis (hazard ratio, 1.81; P  = .0108). For overall survival, testosterone ≥ 1.3 ng/dL (hazard ratio, 3.37; P  < .0001), high volume (hazard ratio, 3.06; P  = .0009), and prostate‐specific antigen ≥ 27.0 ng/mL (hazard ratio, 2.75; P  = .0013) were independent prognostic factors on multivariate analysis. When assessing related clinical factors, higher serum testosterone was associated with visceral metastasis, high volume, and prostate‐specific antigen. Based on three prognostic factors (testosterone, high volume, prostate‐specific antigen), a risk classification was developed. The high‐risk group (3 risk factors) showed a significantly shorter overall survival compared to the moderate‐risk (2 risk factors) and low‐risk (0‐1 risk factor) groups ( P  < .0001). Conclusions: The present study identified higher serum testosterone (≥13 ng/dL) as a significant prognostic factor in castration‐resistant prostate cancer patients treated with docetaxel therapy.